2017
DOI: 10.1080/20786190.2017.1333784
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and correlates of obesity among public service workers in Ondo State, Nigeria: a cross-sectional study

Abstract: Background: Obesity is the third leading cause of mortality and has become a global epidemic. There is a continuous increase in its prevalence both in the developed and in developing countries. Obesity is closely associated with chronic health conditions, thus increasing the overall burden of disease and disability at the population level. Several factors have been identified as contributors to the obesity epidemic, and may include the work environment and lifestyle behaviours. This study sought to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The study findings also revealed that the senior ranked nurses from assistant chief nursing officer to assistant director of nursing had obesity and those on the senior nursing officer and principal nursing officer rank were overweight. These findings were similar to that of Isaac [20], who reported that the prevalence of overweight and obesity were strongly associated with aging (≥ 41 years), female gender and being married. Similarly, [24] reported obesity and increasing age are the major risk factors fueling increased prevalence of type 2 diabetes mellitus among the participants.…”
Section: Discussion Of Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…The study findings also revealed that the senior ranked nurses from assistant chief nursing officer to assistant director of nursing had obesity and those on the senior nursing officer and principal nursing officer rank were overweight. These findings were similar to that of Isaac [20], who reported that the prevalence of overweight and obesity were strongly associated with aging (≥ 41 years), female gender and being married. Similarly, [24] reported obesity and increasing age are the major risk factors fueling increased prevalence of type 2 diabetes mellitus among the participants.…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…There is a continuous increase in obesity prevalence both in developed and developing countries with its associated chronic health conditions, thus increasing the overall burden of disease and disability at the population level. Several factors have been identified as contributors, including the work environment and lifestyle behaviours [20][21][22], the female gender, marriage, low physical activity level, positive family history, the urban area of residence, and age ≥40 years [15] as well as the urban, professional, high socioeconomic variables of Nigerian adults [13].…”
Section: Introductionmentioning
confidence: 99%
“…According to Quintiliani (2008), stated that workplace offers several advantages for promoting physical activity because a substantial number of the workforce can be reached and multiple levels of influence on behaviour can be targeted. Civil servants constitute a large percentage of a nation's workforce and majority of them are at high risk of obesity due to the lifestyle of physical inactivity (Isaac et al, 2017). Considering the key role played by the civil servants in the economy of a nation, it will be highly risky to ignore them as physical inactivity could lead to consortium of diseases which will ultimately affect their health leading to absenteeism from work, low productivity and ultimately take a toll on the nation's economy.…”
Section: Introductionmentioning
confidence: 99%
“…Other characteristics of the distribution of obesity/overweight in Nigeria include its high prevalence along with socioeconomic class and in mid-life [13]- [19] with some studies reporting that more than 55% were either overweight or obese [1] [13]. The peak prevalence of obesity in most studies from Nigeria is midlife [1] [2] [3] [15] [20], while the lowest prevalence of obesity is observed below 20 years [15] [20].…”
Section: Introductionmentioning
confidence: 99%